Prevalence of deficiencies of serum vitamin D3 and vitamin B12 among urban and rural population in and around Pune, India: An observational study - Swati Ghonge; Hetal Rathod; Amitav Banerjee; Shweta Chauhan; Tanu Baxi; Deepu Palal; Jitendra Bhawalkar; Sai Mahesh Vajjala (Journal of Family Medicine and Primary Care)
Introduction: Vitamin D and vitamin B12 deficiencies are major public health problems in many populations. Studies report a deficiency in the range of 20–80% of both micronutrients. Hence, a comparative study was conducted among a rural and an urban population to see the prevalence and factors associated with their deficiency. Methodology: The institutional ethics committee approved the study. Informed consent was taken from all the participants. Cross-sectional comparative analytical study among participants of rural and urban field practice areas of a medical college was undertaken. Measurements were made on 121 participants, 67 from urban areas, and 54 from rural regions. Participants were selected in a simple random sampling technique. Blood samples were collected in a standardized technique following aseptic conditions and transported to the laboratory maintaining a cold chain for analysis. Data were entered into Microsoft Excel and analyzed using Jamovi v2.4.11. Chi-square test, t-tests, and Mann-Whitney U tests were used, and tests of significance with P < 0.05 cut-off for rejecting the null hypothesis. Results: Apart from education, body mass index (BMI), and socioeconomic status, all factors were similar among rural and urban participants. The mean BMI of urban participants was more than rural counterparts. Deficiency of vitamin B12 was 52.2% in urban and 64.8% in rural areas; deficiency of vitamin D was 34.3% in urban and 13% in the rural sample. Mean values of vitamin D and vitamin B12 were significantly different, 17.77 ng/mL vis-a-vis 19.02 ng/mL and 254.82 pg/mL vis-a-vis 185.48 pg/mL, respectively, for urban and rural participants. Vitamin D was more deficient in urban areas, and vitamin B12 was more deficient in rural areas. Conclusion: Both deficiencies found in the participants are of concern and require different interventions. Urban participants should be advised more of outdoor activities, and rural participants should be educated more on dietary interventions. Supplements at the individual level may be advised as needed.